2015
DOI: 10.1021/acs.est.5b03205
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Combustion Conditions and Photochemical Processing on the Light Absorption of Biomass Combustion Aerosol

Abstract: The aim was to identify relationships between combustion conditions, particle characteristics, and optical properties of fresh and photochemically processed emissions from biomass combustion. The combustion conditions included nominal and high burn rate operation and individual combustion phases from a conventional wood stove. Low temperature pyrolysis upon fuel addition resulted in "tar-ball" type particles dominated by organic aerosol with an absorption Ångström exponent (AAE) of 2.5-2.7 and estimated Brown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
130
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 48 publications
16
130
1
Order By: Relevance
“…As the absorption from primary OA (Br-POA) from biofuel and biomass burning typically dominates that of absorbing SOA (Br-SOA) (Martinsson et al, 2015;Laskin et al, 2015), the absorption of Br-SOA is much more challenging to detect than Br-POA in most field measurements. We therefore focus our analysis on the primary sources of BrC.…”
Section: Methods For Deriving Brc Absorption From Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the absorption from primary OA (Br-POA) from biofuel and biomass burning typically dominates that of absorbing SOA (Br-SOA) (Martinsson et al, 2015;Laskin et al, 2015), the absorption of Br-SOA is much more challenging to detect than Br-POA in most field measurements. We therefore focus our analysis on the primary sources of BrC.…”
Section: Methods For Deriving Brc Absorption From Observationsmentioning
confidence: 99%
“…Although we know that BrC is associated with biofuel and biomass burning combustion, the role of fuel source and burning conditions in determining BrC absorption is not well known. Saleh et al (2014) and Martinsson et al (2015) suggest that the absorption of BrC generated from biomass burning is correlated with the BC / OC emission ratio. Various secondary organic aerosol (SOA) precursors are also thought to be a source of BrC, including monoterpenes, isoprene, and nitroaromatic compounds (Laskin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former study reported evidence for the incorporation of nitrogen into SOA. OFRs have also been increasingly employed to process emissions of vehicles, biomass burning, and other combustion sources (Table 1) in which NO can often be hundreds of ppm Martinsson et al, 2015;Karjalainen et al, 2016;Link et al, 2016;Schill et al, 2016;Alanen et al, 2017;Simonen et al, 2017). It can be expected that such a high NO input together with very high VOC concentrations would cause a substantial deviation from the good OFR operation conditions identified in Peng et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, organic aerosol (OA) is known to mainly scatter incoming sunlight, thereby cooling the climate. Recently, the strongly ultraviolet-absorbing brown carbon (BrC) has gained attention in the scientific community (Laskin et al, 2015;Martinsson et al, 2015;Saleh et al, 2013Saleh et al, , 2014. BrC is emitted in large quantities from wood burning and has been proposed to affect lower tropospheric photochemistry by reducing ultraviolet (UV) radiation (Jacobson, 1999).…”
mentioning
confidence: 99%